Department of Environment and Natural Resources - 1 employees multi-purpose cooperative - Banez, Nellie T. (La Union : [s.n.], 2012)
This study analyzed the management of the Department of Environment and Natural Resources-I Employees Multi-Purpose Cooperative (DENR-1 EMPC), which is located at Government Center, Brgy. Sevilla, City of San Fernando, La Union. Specifically, this undertaking aimed to present the company profile; describe its various systems such as organization and human resource management, operations management, marketing management and financial management; analyze the various systems by identifying the strengths, opportunities. recommendations based on the SWOT results. This study was a descriptive type of research using the case study approach. The general profile of the cooperative was gathered, consolidated and analyzed to show the situational analysis utilizing the SWOT analysis. The profile presented the following: DENR-I EMPC was organized in the early part of the year 2000 and registered with the Cooperative Development Authority (CDA) on December 1, 2000. With the passing of a new law, the cooperative was again registered under CDA9520- 01016774. Using the SWOT analysis, the following were found: The strong points in the operations and human resource management of the cooperative were on its active members, elected board of directors, presence of operations manual, and reasonable compensation of management staff. Weak points were on the two staffs, who were both Bookkeepers; each committee had only one member; limited term of each board of director; absence of a salary scale; no fixed compensation of officers; limited services offered to members; and less than 50% of the employees of DENR-1 are member. There was an opportunity to attend seminars and trainings by CDA. Membership was being threatened by the rationalization of DENR-1. On the operations management of the cooperative, strong points were revealed such as the high interest rate on deposits, enough funds to finance the loan requirements, and the presence of a variety of loun service. Weak points were noted such as the too high deposit requirement, high past due accounts, loans is approved by the General Manager, and the fast loan releases. There is an opportunity on re- discounting of check. Other lending companies threatened the operations of the cooperative. On marketing management, strengths were on the competitive interest rates, variety of loans, accessible office location, promotional materials or stuffs given to members, as well as the patronage refund and dividends. However, weaknesses were on the payment of monthly rent and the non-compliance to the manual on the maximum amount of emergency loan. On financial management, the cooperative is strong on the use of the double entry bookkeeping, payment of loans through salary deduction, use of checks for disbursement, and high liquidity and profitability ratios, Weak points were on the delayed financial statement reporting to CDA, high leverage ratios, manual record keeping, high loan receivables, no surety bond for officers signing checks, and not proper observance of the mandated allocation of Community Development Funds. There is an opportunity on the use of computerized program for accounting. The cooperative might be declared "non-operating for failure to promptly submit the CDA requirements. Based on the SWOT findings, recommendations are as follows: strong points in all management systems are to be maintained. On the organization and human resource management: the Cooperative should have only one bookkeeper, update the operations manual, add members to committees, consider the proposed organizational chart; not limit the term of office of board members, provide a salary scale, fix the benefits of the board directors in the by-laws; provide other cooperative services, let the officers and members attend seminars and trainings, and train potential managers as cushion to rationalization. In addressing the weak points of the operations, the Cooperative should lower the amount of minimum deposit, undertake legal action for past due accounts; use the credit committee for loan processing, lengthen loan processing to two days more for big amount and rediscount checks. Relative to marketing management, although the location is highly accessible, the office rent should not be paid to DENR-1 because of the application of RA 9520. On financial management, the cooperative should adhere to the requirements of CDA, adopt a computerized accounting system, and implement the operations manual. The officers or in-charge of signing checks and safeguarding the property should post surety bond and the cooperative should allocate at least 3% of the net surplus for the Community Development Fund.
Bibliography: pages 109-110.
CHED-La Union
Keywords: Cooperative agriculture